2022
DOI: 10.1038/s41385-021-00477-5
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbe-dependent ω3 lipid metabolite αKetoA prevents inflammatory diseases in mice and cynomolgus macaques

Abstract: Dietary ω3 fatty acids have important health benefits and exert their potent bioactivity through conversion to lipid mediators. Here, we demonstrate that microbiota play an essential role in the body’s use of dietary lipids for the control of inflammatory diseases. We found that amounts of 10-hydroxy-cis-12-cis-15-octadecadienoic acid (αHYA) and 10-oxo-cis-12-cis-15-octadecadienoic acid (αKetoA) increased in the feces and serum of specific-pathogen-free, but not germ-free, mice when they were maintained on a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 73 publications
(90 reference statements)
0
24
0
Order By: Relevance
“…We did not evaluate the alterations in gut microbiota in the present study. Nonetheless, previous studies performed by ourselves, and by others, revealed that various PUFAs (including GLA) have beneficial actions on gut microbiota [ 95 , 96 , 97 ]. Hence, one distinct possibility by which GLA is beneficial against radiation can be ascribed to its ability to alter gut microbiota (See Figure 18 ).…”
Section: Discussionmentioning
confidence: 94%
“…We did not evaluate the alterations in gut microbiota in the present study. Nonetheless, previous studies performed by ourselves, and by others, revealed that various PUFAs (including GLA) have beneficial actions on gut microbiota [ 95 , 96 , 97 ]. Hence, one distinct possibility by which GLA is beneficial against radiation can be ascribed to its ability to alter gut microbiota (See Figure 18 ).…”
Section: Discussionmentioning
confidence: 94%
“…In this diet-induced model, male mice are generally used because they are more susceptible to diet-induced weight gain and diabetic pathology 89 , but it is also necessary to examine the sexual differences of the effects of B. wexlerae in the future study including human. As done in previous studies 90,91 , we fasted our mice for 16 h; however, this might have been excessive and thus induced metabolic changes that occur during starvation. Furthermore, although we focused on the metabolism of adipose tissue as a possible mechanism of the control of obesity and diabetes, liver has an even greater role than adipose tissue in energy metabolism, such that more comprehensive studies including assessments using metabolic cages are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry was performed as described previously, with slight modification 91,102 . Cells in the stromal vascular fraction of eAT were Article https://doi.org/10.1038/s41467-022-32015-7…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, α-linolenic acid is metabolised by Lactobacillus plantarum AKU 1009a to generate the bioactive metabolite 10-oxo-cis-12-cis-15-octadecadienoic acid (α-Keto acid) [ 77 ]. Interestingly, pioneering research has shown that anti-inflammatory properties are retained by α-Keto acid [ 78 ]. The authors revealed that α-Keto acid was capable of inducing M2 macrophage polarisation in mice administered a high-fat diet.…”
Section: Dietary Approaches For Targeting Macrophage Plasticitymentioning
confidence: 99%